LAW ENFORCEMENT PREPAREDNESS FOR THE IMPLEMENTATION OF INDONESIA’S LAW ON JUVENILE JUSTICE SYSTEM - Dani Krisnawati (Fakultas Hukum Universitas Gadjah Mada, 2013)
Paradigmatic changes stipulated in Law Number 11 of 2012 on Juvenile Justice System, including regulations concerning restorative justice and diversion require the competency and skills of the law enforcement officers. This research identifies measures that have been taken and the existing barriers in preparing for the implementation of this Law. The research demonstrates that the readiness of the investigators and child prosecutors are merely limited to the outreach of Law Number 11 of 2012, whilst knowledge of the court judges only covers the draft Law. The number of officers receiving outreach is limited and should be increased. Negative perception on the officers due to the risk of a bribery accusation is feared to hamper the implementation of diversion regulation based on a restorative justice. Perubahan paradigmatik yang termuat dalam Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak, termasuk diantaranya ketentuan mengenai keadilan restoratif dan diversi, memerlukan kompetensi dan keahlian aparat penegak hukum. Penelitian ini mengidentifikasi langkah yang telah dilakukan dan kendala persiapan implementasi Undang-Undang tersebut. Hasil penelitian memperlihatkan bahwa kesiapan penyidik dan penuntut umum anak masih terbatas pada partisipasi sosialisasi Undang-Undang Nomor 11 Tahun 2012, sedangkan hakim anak memiliki pengetahuan hanya pada Rancangan Undang-Undang. Jumlah aparat yang menerima sosialisasi Undang-Undangmasih terbatas dan perlu ditingkatkan jumlahnya. Pandangan negatif terhadap aparat karena bisa menimbulkan dugaan suap dikhawatirkan menjadi penghambat diterapkannya ketentuan diversi dengan pendekatan keadilan restoratif.